Correction to: Length of hospitalization is associated with selected biomarkers (albumin and lymphocytes) and with co-morbidities: study on 4000 patients - Antonio E. Pontiroli; Lara Loreggian; Marco P. L. Rovati; Elena De Patto; Laura Folini; Federico Raveglia; Matilde De Simone; Alessandro Baisi; Ugo Cioffi (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.